2021
DOI: 10.1007/s00170-021-08384-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the influence of reinforcing fiber type on the grinding process of PEEK’s composites

Abstract: Polyether ether ketone (PEEK) and its composites are widely used in the biomedical industry due to their superior properties. The presence of glass and carbon reinforcing particles will improve the strength of the polymers while affecting their machinability. The cutting speed, dressing speed ratio, and different reinforcing fibers were defined as input parameters. Grinding forces, specific grinding energy, surface roughness, the surface topography of the workpiece, and wheel loading ratio were selected as out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Kamplade and Biermann 15 showed that it could be due to an increment in the rubbing and plowing portion (the increase in normal force is higher than in tangential force at higher cutting speeds). The result conducted from the study of Khoran et al 12 also conforms with this outcome. The PEEK grinding force was higher than its composites due to more rubbing and plowing.…”
Section: Force Ratiosupporting
confidence: 71%
See 1 more Smart Citation
“…Kamplade and Biermann 15 showed that it could be due to an increment in the rubbing and plowing portion (the increase in normal force is higher than in tangential force at higher cutting speeds). The result conducted from the study of Khoran et al 12 also conforms with this outcome. The PEEK grinding force was higher than its composites due to more rubbing and plowing.…”
Section: Force Ratiosupporting
confidence: 71%
“…Comparing the specific energies of the single grit scratch test and the grinding process 8,12 shows that the specific energy of the grinding is higher than that of the single grit test. Because several mechanisms like loading influence the specific energy in the grinding process, which does not happen in the single grain test.…”
Section: Specific Energymentioning
confidence: 99%
“…During sample grinding, heating and an increase in the exchange surface area may occur, allowing some free water to evaporate. 73,74…”
Section: Resultsmentioning
confidence: 99%
“…During sample grinding, heating and an increase in the exchange surface area may occur, allowing some free water to evaporate. 73,74 Distribution of water content across the scrapped outlet guide vanes Mapping. In order to represent the water content distribution across an OGV blade, a NACA 4-digit airfoil is used.…”
Section: Water Content By Karl Fischer Titrationmentioning
confidence: 99%
“…The results showed that as the temperature of the machining area increased, the material entered a visco-elastic state and the quality of the milled surface deteriorated. Khoran et al [ 19 , 20 ] studied the grinding performance of PEEK, carbon-fiber-reinforced PEEK and glass-fiber-reinforced PEEK. The results showed that the machining temperature had a greater impact on the surface quality of PEEK and fiber-reinforced PEEK, while when using liquid nitrogen as the coolant, the grinding surface quality was significantly improved.…”
Section: Introductionmentioning
confidence: 99%